PEMANFAATAN MEDIA SOSIAL DALAM KEHUMASAN DIGITAL KEMENTERIAN LUAR NEGERI - Nugraha, Punjul Setya; Irwansyah, Irwansyah (Interaksi: Jurnal Ilmu Komunikasi, 2022)
As a mode of technology mediated communication, the advent and development of social media has provided a vast array of interaction, which may lead to the attainment of understanding between public and government. Using Kent & Taylor’s model on dialogic two-way models, an organization could deliver an effective, sophisticated, and effective public relation programs using social media. Social media plays a significant role in providing avenues for such a high degree interaction. A successful public relation campaign, in the end, would contribute greatly in an organization’s efforts to manage its image. This article is aimed at providing elaboration on ways through which a government institution could effectively utilize social media in its public relations campaign, using a qualitative descriptive approach. This article found that the degree of social media utilization by a government institution would very much be depended on their respective social media adoption stage.